A Comparitive Evaluation of Sealing Ability, pH and Rheological Properties of Zinc Oxide Eugenol Sealer Combined with Different Antibiotics: An In Vitro Study - D. Binoy (Journal of Clinical and Diagnostic Research, 2014)
Aim: The objective of this study was to evaluate and compare the sealing ability, pH & viscosity of Zinc oxide eugenol sealer mixed with different antibiotics (Amoxicillin, Ciprofloxacin, Clindamycin and Doxycycline). Materials and Methods: Ninety single rooted anterior teeth were randomly divided into four experimental groups of 15 teeth each and 3 control groups of 10 each. Sealer-antibiotic combination was used as a sealer in experimental group. Teeth were sectioned longitudinally to assess linear dye penetration. pH and viscosity of the experimental groups were evaluated with Elico pH Meter and Brook Field Viscometer respectively. Results: (Amoxicillin+ ZOE) Group II and (Clindamycin + ZOE) Group IV have shown minimum linear dye leakage of 1.07mm & 1.22 mm respectively & (Ciprofloxacin + ZOE) Group III and (Doxycycline + ZOE) Group V 2.69 mm & 2.59 mm respectively. There was decrease in the viscosity of the experimental group. pH was found to be 8.55 for Group II sealer which was greater than control group. Conclusion: Amoxicillin and sealer combination can improve the success rate of endodontic therapy by enhancing the antimicrobial activity, alkaline environment and reducing apical microleakage.